Foreign Investment, Corporate Ownership, and Development: Are Firms in Emerging Markets Catching Up to the World Standard? - Peter, Klara Sabirianova; Svejnar, Jan; Terrell, Katherine (The Review of Economics and Statistics, 2012)
Economic development implies that the efficiency of firms in developing countries starts approaching that of firms from advanced economies. Various development policies have been pursued to achieve this convergence. We test for this convergence in two economies that represent alternative models of implementing market-oriented development policies: the Czech Republic and Russia. Using 1992–2000 panel data on virtually all medium and large industrial firms in each country and accounting for endogeneity of ownership, we find that foreign ownership markedly improved the efficiency of firms, whereas domestic private ownership did not; domestic firms are not catching up to the (world) efficiency standard given by foreign-owned firms. This is due in part to a slower growth of efficiency in domestic firms over time. However, foreigners' acquisitions of more efficient domestic firms are also contributing to the gap. Domestic firms closer to the frontier are not more likely to catch up than firms farther from the frontier, although foreign firms do exhibit this behavior. The distance of Russian firms to the efficiency frontier is much larger than that of Czech firms. Nevertheless, after nearly a decade of reforms, neither model of development has resulted in convergence of domestic firms to the world standard.